On the type species of the genus Dendarus Dejean, 1821 (Coleoptera: Tenebrionidae) - Kamiński, Marcin Jan; Bouchard, Patrice; Leo, Piero; Iwan, Dariusz (Zootaxa, 2021)
Based on type specimen investigation, the status of Helops tristis Rossi, 1790 as the type species of the genus Dendarus Dejean, 1821 is confirmed. Lectotypes are designated for Helops tristis and Pandarus coarcticollis Mulsant, 1854 – both are classified in Dendarus. Pandarus libanicus Desbrochers des Loges, 1881 is recognised as a junior synonym of Dendarus calcaratus Baudi di Selve, 1881. Both taxa share the same locus typicus (Mount Lebanon in Lebanon) and are morphologically distinct from the Italian Dendarus lugens (Mulsant & Rey, 1854). Finally, D. lugens is considered as a synonym of D. (Dendarus) coarcticollis.